2021
DOI: 10.1016/j.ijid.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium tuberculosis genotypes and their correlation to multidrug resistance in Lusaka, Zambia

Abstract: The burden of multidrug-resistant tuberculosis (MDR-TB) has been reported to be increasing in Zambia. The reasons for the increase are still unclear. This study determined the diversity of Mycobacterium tuberculosis genotypes among isolates in Lusaka, the capital city, and investigated their association with MDR-TB. Methods: Spoligotyping, large sequence polymorphism (LSP) analysis, and sequencing of MDR associated genes were performed on a total of 274 M. tuberculosis clinical isolates stored at the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Spoligotyping was conducted as previously described [5,43]. Briefly, the direct repeat region was amplified by PCR using primers DRa GGTTTTGGGTCTGACGAC and DRb CCGAGAGGGGACGGAAAC, and the resulting products were hybridized to 43 spacerspecific oligonucleotide probes on a membrane.…”
Section: Spoligotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Spoligotyping was conducted as previously described [5,43]. Briefly, the direct repeat region was amplified by PCR using primers DRa GGTTTTGGGTCTGACGAC and DRb CCGAGAGGGGACGGAAAC, and the resulting products were hybridized to 43 spacerspecific oligonucleotide probes on a membrane.…”
Section: Spoligotypingmentioning
confidence: 99%
“…This practice could have led to the undetected emergence and silent spread of drug-resistant TB. In a previous study, it was demonstrated that the increase in MDR-TB in Zambia is not the result of transborder transmission but local emergence and possible spread within Zambia [4,5]. The mismanagement of MDR-TB could further the evolution of resistance to other anti-TB drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies in Zambia have described M. tuberculosis diversity using 15 loci MIRU-VNTR in Ndola and Namwala districts (Mulenga et al 2010;Malama et al 2014). Further, we previously described an association of drug resistance with specific genotypes in Lusaka based on spoligotyping (Solo et al 2020b). Nevertheless, information on the transmission of MDR M. tuberculosis strains in Lusaka, Zambia is still inadequate.…”
Section: Introductionmentioning
confidence: 97%
“…L4 is phylogenetically complex, with at least ten distinct sublineages that differ in geographical distribution, with local genotypes accounting for a larger proportion of circulating strains in certain regions [ 15 ]. For instance, the L4-Cameroon family is almost exclusively found in West Africa [ 14 ] while the Latin American-Mediterranean (LAM) family is most predominant in Zambia [ 38 , 39 ]. Similarly, the L4-U family is more predominant in Uganda as opposed to anywhere else [ 4 , 28 , 31 , 40 ].…”
Section: Discussionmentioning
confidence: 99%